Breeding feasibility of Pteronymia zerlina and P. medellina (Lepidoptera: Danainae: Ithomiini) - BOLAÑOS-MARTÍNEZ, IVÓN ANDREA; ZAMBRANO-GONZÁLEZ, GISELLE (Revista Colombiana de Entomología, 2011)
Knowledge of the biology of the different species of butterflies is of great importance to propose plans of sustainable development, ecotourism, environmental education and conservation of ecosystems. In this study of breeding feasibility, information is provided on survivability under two breeding systems, in situ and ex situ, of Pteronymia zerlina and P. medellina. A manual collection of the immature butterfly stages was conducted. For the in situ breeding, host plants with eggs were identified in the forest and the life cycle was followed there. For the ex situ breeding, eggs were collected and transported to a breeding laboratory. The breeding feasibility was determined by means of mortality rates and survival rates. The ex situ breeding of P. zerlina presented 64.7% survival and the in situ 22.9%. The ex situ breeding of P. medellina presented 63% and 42% under in situ conditions. The ex situ breeding showed higher breeding probabilities.